Bill Payment And Package Delivery Procedure At The Company Pt Pos Indonesia Cikutra Branch Office - Ai Nunung; Dian Candra Fatihah; Euis Hernawati; Sandy Ramadan Ismail (SEAN Institute, 2024)
This research aims to determine the Bill Payment and Package Delivery Procedure at the PT Pos Indonesia Company, Cikutra Branch Office. The research method used is a qualitative method with a descriptive approach, data collection techniques using interviews, observation and literature review which have close relevance to the procedure. From the research results, it is clear that the online system at PT POS Indonesia Cikutra Branch Office will only start in 2021 with the release of Pospay and PosAja PT Pos Indonesia, which currently still have a period of development. PT Pos Indonesia's Pospay and Pos Aja applications are not fully running perfectly, so there are still many people who use them offline, namely visiting the nearest post office for reasons of limited ability and knowledge in using the Pospay application. Most people, especially those who are elderly, prefer to visit the post office to send packages because the PosAja application cannot make deliveries outside the city with a maximum weight that cannot exceed 5 kg. The problem encountered is that the server often experiences downtime in the Pospay application, causing long queues and taking a long time to complete. The advice that the author can give is to upgrade offline and online service procedures for bill payments and package delivery as well as routinely and periodically upgrade the service system on the Pospay and PosAja applications so that it is hoped that the application developers from PT Pos Indonesia can continue to demonstrate their abilities so that the application is successful. now it can be continuously updated for the sake of a digital era that is practical and easy.